The benzodiazepine-like natural product tilivalline is produced by the entomopathogenic bacterium Xenorhabdus eapokensis - Wolff, Hendrik; Bode, Helge B. (PLOS ONE, 2018)
The pyrrolobenzodiazepine tilivalline (1) was originally identified in the human gut pathobiont Klebsiella oxytoca, the causative agent of antibiotic-associated hemorrhagic colitis. Here we show the identification of tilivalline and analogs thereof in the entomopathogenic bacterium Xenorhabdus eapokensis as well as the identification of its biosynthesis gene cluster encoding a bimodular non-ribosomal peptide synthetase. Heterologous expression of both genes in E. coli resulted in the production of 1 and from mutasynthesis and precursor directed biosynthesis 11 new tilivalline analogs were identified in X. eapokensis. These results allowed the prediction of the tilivalline biosynthesis being similar to that in K. oxytoca.